The African garrison state : human rights & political development in Eritrea / Kjetil Tronvoll & Daniel R. Mekonnen. - Tronvoll, Kjetil; Mekonnen, Daniel Rezene (Boydell & Brewer, 2014)
When Eritrea gained independence in 1991, hopes were high for its transformation. In two decades, however, it became one of the most repressive in the world, effectively a militarised "garrison state". This comprehensive and detailed analysis examines how the prospects for democracy in the new state turned to ashes, reviewing its development, and in particular the loss of human rights and the state's political organisation. Beginning with judicial development in independent Eritrea, subsequent chapters scrutinise the rule of law and the court system; the hobbled process of democratisation, and the curtailment of civil society; the Eritrean prison system and everyday life of detention and disappearances; and the situation of minorities in the country, first in general terms and then through exploration of a case study of the Kunama ethnic group. While the situation is bleak, it is not without hope, however: the conclusion focuses on opposition to the current regime, and offers scenarios of regime change and how the coming of a second republic may yet reconfigure Eritrea politically. Kjetil Tronvoll is Professor of Peace and Conflict Studies at Bjoerknes College, founding and senior partner of the International Law and Policy Institute, Oslo, and a former Professor of Human Rights at the University of Oslo; Daniel R. Mekonnen is Senior Legal Advisor, International Law and Policy Institute, Oslo, and former Judge of the Zoba Maekel Provincial Court in Eritrea.